Peningkatan Hasil Belajar Kognitif Siswa dengan Menggunakan Metode Numbered Heads Together (NHT) dalam Pelajaran Biologi Kelas VII di SMPK Medan - Leticya Sarung Allo; Desri Kristina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2016)
Students grade VII’s cognitive learning outcomes at SMPK Medan were relatively low. It was caused by many factors, one of them was the learning method which was still conventional. Students were needed to improve their learning outcomes, so the researcher made the research with purpose was to know the improvement ofstudents’ learning outcomes by using Numbered Heads Together (NHT) method. The research methodology was used quasi experimental with nonequivalent control group design. The samples of this research were students at grade VII A and VII B. Grade VII B as experimental class and grade VII A as control class. Both of the classes were given treatment, the experimental class with NHT and control class with conventional learning. The improved of learning outcomes can be seen from the mean of N -Gain in experimental class was 0.39 in middle category and the control class was 0.09 in low category. The control class and experiment class had different learning result significantly. Based on the research, it can be concluded that this method can increased students’ learning outcomes at grade VII at SMPK Medan. Keywords: NHT, conventional learning, learning outcomes